IMPROVING ISLAMIC RELIGIOUS EDUCATION LEARNING OUTCOMES ON THE TOPIC OF TELLING THE STORY OF THE PROPHET THROUGH THE METHODS OF GIVING LEARNING ASSIGNMENTS AND RECITATIONS AT SD NEGERI 12 TANGAN-TANGAN - Isnawati; Nursimah (Jurnal Pendidikan Profesi Guru, 2025)
Teachers act as managers of the teaching and learning process, acting as facilitators who try to create effective teaching and learning conditions, so as to enable the teaching and learning process, develop good learning materials, and improve students' ability to listen to lessons and master the educational goals they must achieve. This requires changes in organizing classes, the use of teaching methods, teaching and learning strategies, as well as the attitudes and characteristics of teachers in managing the teaching and learning process. Islamic Religious Learning no longer prioritizes absorption through achieving information, but rather prioritizes the development of abilities and information processing. For this reason, student activities need to be increased through exercises or assignments by working in small groups and explaining ideas to others. The purpose of this study is to improve student learning achievement. This study uses Classroom Action Research (CAR). Based on the results of the study, students experienced an increase, this can be seen from the good understanding and completeness of student learning in a classical manner that has been achieved.